2019
DOI: 10.1021/acs.nanolett.8b05148
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo High-resolution Ratiometric Fluorescence Imaging of Inflammation Using NIR-II Nanoprobes with 1550 nm Emission

Abstract: Quantitatively imaging the spatiotemporal distribution of biological events in living organisms is essential to understand fundamental biological processes. Self-calibrating ratiometric fluorescent probes enable accurate and reliable imaging and sensing, but conventional probes using wavelength of 400–900 nm suffer from extremely low resolution for in vivo application due to the disastrous photon scattering and tissue autofluorescence background. Here, we develop a NIR-IIb (1500–1700 nm) emissive nanoprobe for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(178 citation statements)
references
References 56 publications
3
173
0
2
Order By: Relevance
“…13 Very few inorganic NIR-IIb uorophores such as single-walled carbon nanotubes (SWNTs), rare earth doped nanoparticles, and quantum dots have been investigated for biosensing and bioimaging beyond 1500 nm. 7g,8f, [13][14][15][16][17] It is worth noting that organic FD-1080 J-aggregates were rst accomplished with high resolution imaging of the cerebral and hindlimb vasculature with uorescence emission tailing into 1500 nm with a quantum yield (QY) of 0.0545%. 17 The signal-tobackground ratio (SBR) was 3.3-fold higher than that of NIR-IIa (1300-1400 nm) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…13 Very few inorganic NIR-IIb uorophores such as single-walled carbon nanotubes (SWNTs), rare earth doped nanoparticles, and quantum dots have been investigated for biosensing and bioimaging beyond 1500 nm. 7g,8f, [13][14][15][16][17] It is worth noting that organic FD-1080 J-aggregates were rst accomplished with high resolution imaging of the cerebral and hindlimb vasculature with uorescence emission tailing into 1500 nm with a quantum yield (QY) of 0.0545%. 17 The signal-tobackground ratio (SBR) was 3.3-fold higher than that of NIR-IIa (1300-1400 nm) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Within the NIR‐II window, several studies have confirmed increased imaging resolution by using NIR‐II b (1500–1700 nm) emitting probes . Among these materials, Er 3+ ‐doped rare‐earth nanocrystals exhibiting efficient downshifted luminescence (1525 nm) in this wavelength region are applied for in vivo bioimaging . However, one nonnegligible issue is that the previously reported excitation wavelength is mostly located at NIR‐I region such as 808 nm and 980 nm owing to the limited sensitizers (Yb 3+ , Nd 3+ ) .…”
Section: Figurementioning
confidence: 99%
“…[77] The nanoprobe SPNP25 is achieved through blending a ClO − -responsive nonfullerene acceptor 3,9-bis(2-methylene- ( (Figure 7d-f). [78] In this system, excitation wavelength is used at 808 nm, i.e., in the absorption overlapping region, the NIR-II fluorescence of DCNPs is very weak because of the energy filtration by strong absorbance of Cy7.5 at 808 nm under the DCNPs. Under ClO − environment, the Cy7.5 is degraded and thus reversed the Images of e) 980 nm and f) 1180 nm and g) ratiometric (F 980 /F 1180 ) channels of microneedle patches for lipopolysaccharide-induced inflammation at each time points.…”
Section: Hocl/clo − Activationmentioning
confidence: 99%